Process improvement : a handbook for managers - Cook, Sarah, 1955- (Gower, 1996)
"Sarah Cook's latest book offers a systematic, customer-focused approach to improving the way we work. The methods it describes can be applied equally to a specific area or function and to the organization as a whole."--BOOK JACKET. "The author outlines a four-stage approach and shows what is involved at each stage and how to use the relevant techniques. The text is supplemented by case studies drawn from a variety of businesses and notes on sources of further information."--BOOK JACKET. "For managers, team leaders, trainers and consultants looking for practical ways to enhance organizational performance, here is a powerful new tool."--BOOK JACKET.